Analysis of the sociodemographic characteristics and academic factors that affect the completion efficiency of the TECNM/ITSLP - Rosales Escobar, María Leonor; Navarrete Sánchez, María Eugenia; Garcés Rodríguez, Ángela Rebeca (IE Revista de Investigación Educativa de la REDIECH, 2024)
The objective of this research is to analyze the sociodemographic characteristics and the academic factors that are significant to achieve terminal efficiency in the TecNM/ITSLP. The study is descriptive, with a quantitative approach. Three cohorts were studied with data obtained from the Integral Information System. The Chi square test was applied for the analysis of independence of the study variables, with a = 0.05. To determine the characteristics and significant factors that affect the achievement of terminal efficiency, the Multivariate Binary Logistic Regression analysis was used, with 13 degrees of freedom and a = 0.05; the results show that sex, age, educational level of the father, the arithmetic average in the 1st year of the degree and the number of failed subjects are highly significant to achieve terminal efficiency. To complement this study, a survey was applied to students from the 7th to the 12th semester, from which it was obtained that the impediments they have to graduate at the end of their career in order of importance are: the certification of the second language (English), the assignment of the titling project and the proof of social service, among others.